Tomato Root Growth Inhibition by Salinity and Cadmium Is Mediated By S-Nitrosative Modifications of ROS Metabolic Enzymes Controlled by S-Nitrosoglutathione Reductase - Jedelská, Tereza; Kraiczová, Veronika Šmotková; Berčíková, Lucie; Činčalová, Lucie; Luhová, Lenka; Petřivalský, Marek (Biomolecules, 2019)
S-nitrosoglutathione reductase (GSNOR) exerts crucial roles in the homeostasis of nitric oxide (NO) and reactive nitrogen species (RNS) in plant cells through indirect control of S-nitrosation, an important protein post-translational modification in signaling pathways of NO. Using cultivated and wild tomato species, we studied GSNOR function in interactions of key enzymes of reactive oxygen species (ROS) metabolism with RNS mediated by protein S-nitrosation during tomato root growth and responses to salinity and cadmium. Application of a GSNOR inhibitor N6022 increased both NO and S-nitrosothiol levels and stimulated root growth in both genotypes. Moreover, N6022 treatment, as well as S-nitrosoglutathione (GSNO) application, caused intensive S-nitrosation of important enzymes of ROS metabolism, NADPH oxidase (NADPHox) and ascorbate peroxidase (APX). Under abiotic stress, activities of APX and NADPHox were modulated by S-nitrosation. Increased production of H2O2 and subsequent oxidative stress were observed in wild Solanumhabrochaites, together with increased GSNOR activity and reduced S-nitrosothiols. An opposite effect occurred in cultivated S. lycopersicum, where reduced GSNOR activity and intensive S-nitrosation resulted in reduced ROS levels by abiotic stress. These data suggest stress-triggered disruption of ROS homeostasis, mediated by modulation of RNS and S-nitrosation of NADPHox and APX, underlies tomato root growth inhibition by salinity and cadmium stress.
Keywords: Nitric Oxide; root growth; Ascorbate Peroxidases; oxidační stres; aldehydoxidoreduktasy; Pyrroles; S-nitrosoglutathione reductase; reaktivní formy kyslíku; NADPH-oxidasy; S-nitrosothioly; reaktivní formy dusíku; Sodium Chloride; Solanum habrochaites; Plant Roots; Nitrosation; benzamidy; S-nitrosation; peroxid vodíku; oxid dusnatý; nitric oxide; pyrroly; Solanum; Hydrogen Peroxide; chlorid sodný; Benzamides; Plant Proteins; regulace genové exprese u rostlin; Solanum lycopersicum; kořeny rostlin; Stress, Physiological; Reactive Oxygen Species; S-Nitrosothiols; Gene Expression Regulation, Plant; abiotic stress; Reactive Nitrogen Species; nitrosace; askorbátperoxidasa; Cadmium; cadmium; S-Nitrosoglutathione; kadmium; reactive oxygen species; Oxidative Stress; fyziologický stres; salinity; NADPH Oxidases; S-nitrosoglutathion; rostlinné proteiny; Aldehyde Oxidoreductases